Difficulties that students face when learning algebraic problem-solving - Chan, Li Ying (Horizon Research Publishing, 2020)
Algebraic problem-solving is a way of thinking and reasoning that allows students to create models, study relationships, and solve problems. However, students only have a little understanding of formulating and solving algebraic problems. This study aims to determine the predominant difficulties that Year Six students face when learning algebraic problem-solving. This study used a quantitative research design involving 80 students selected by purposive sampling. The instruments used in this study include criterion-referenced tests consisting of word and diagram algebraic problem-solving items. Data were analysed using GNU PSPP software. The descriptive statistics showed that the predominant difficulty that Year Six students faced when solving algebraic word problems was text difficulties and unfamiliar contexts. For diagrammatic algebraic problem-solving, students encountered the most difficulty with visual-spatial awareness. The Chi-Square test was used to identify the statistical correlation coefficient between gender and difficulties in solving algebraic problems. The result showed a positive association between gender and recognition difficulties and gender and sign substitution error. The findings of this study may encourage students to better learn algebraic problem-solving skills. Moreover, this study also provides important information for teachers to better teach algebraic problem-solving to Year Six students.